Protective effect of leflunomide against oxidative intestinal injury in a rodent model of sepsis - Ozturk, Erdogan; Surucu, Murat; Karaman, Abdurrahman; ŞAMDANCI, EMİNE; Fadillioglu, Ersin (My University, 2014)
Background: Sepsis is defined as an uncontrolled inflammatory response in a host. The process may lead to severe sepsis, multisystem organ failure and even death. Leflunomide has important immunomodulatory and anti-inflammatory effects, which may mitigate host response to bacterial translocation. The goal of our study was to measure the effects leflunomide administration had on a variety of biochemical markers upregulated in systemic inflammatory response syndrome, sepsis, and multiple organ failure syndrome.